Functional-interactive function of linguistic and narrative signs in Kurdish pastoral stories (Case study of the stories of Khaumirabad section of Marivan city) - Srweh Fatahi; Narges Jaberinasab; Ahmad Khatami (مطالعات زبانی و بلاغی)
Pastoral tales, as one of the most important type of oral texts, have intra-textual and extra-textual features related to the situational context of the text. Kurdish pastoral are an arena of confrontation for binary opposition the interpretation of which, at both linguistic and narrative levels, will reveal aspects of structural and semantic structure of the text. The present study has tried to study binary oppositions in Kurdish pastoral tales at both narrative and linguistic levels from a semiotic approach. To this end, ideas from linguists and cultural semioticians as well as structuralists’ views in the field of narration have been employed. The results of the research show that, in Kurdish pastoral tales, the hero on quest challenges oppositions and negative semantemes in order to reach the valuable object and the desired world. In this procedure, the hero considered as a cognitive agent and the self belonging to a culture, interacts with the ecosystem of "other" and "another." The hero then achieves the desired result in a process of “removing alterity”  or ”fighting against the other” Eventually, by rejecting the alien world and the undesirable other, he returns to his culture and the world in which peace and balance is restored.